Psychometric Properties of Death Depression Scale in Women with Breast Cancer - MA Soleimani; N Dalvand; S Zarabadi Pour; Z Alimoradi; A GÖRGÜLÜ; N Bahrami (مجله اپیدمیولوژی ایران, 2021)
Background and Objectives: Accurate assessment of patients' death depression requires a specific tool that is appropriate to the culture of each community. Therefore, the aim of this study was to evaluate the psychometric properties of the Death Depression Scale in women with breast cancer.